2008
DOI: 10.1375/twin.11.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Influences on Thought Problems in 7-Year-Olds: A Twin-Study of Genetic, Environmental and Rater Effects

Abstract: T he Thought-Problem scale (TP) of the CBCL assesses symptoms such as hallucinations and strange thoughts/behaviors and has been associated with other behavioral disorders. This study uses parental reports to examine the etiology of variation in TP, about which relatively little is known, in 7-year-old twins. Parental ratings on TP were collected in 8,962 7-year-old twin pairs. Because the distribution of TP scores was highly skewed scores were categorized into 3 classes. The data were analyzed under a thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…However, scores on maternal ratings were, on average, higher than scores on paternal ratings for all problem scales, i.e., mothers report on average more behavioral and emotional problems of their children than fathers did. This is in agreement with prior studies in 7‐year‐old children using different scales of the CBCL [van der Valk et al, ; Boomsma et al, ; Abdellaoui et al, ; Langberg et al, ; Mascendaro et al, ]. Since the cutoffs for subclinical or clinical scores as defined in the manual are the same for maternal and paternal ratings, children rated by their mother will more often pass the threshold than children rated by their father due to this difference between raters.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, scores on maternal ratings were, on average, higher than scores on paternal ratings for all problem scales, i.e., mothers report on average more behavioral and emotional problems of their children than fathers did. This is in agreement with prior studies in 7‐year‐old children using different scales of the CBCL [van der Valk et al, ; Boomsma et al, ; Abdellaoui et al, ; Langberg et al, ; Mascendaro et al, ]. Since the cutoffs for subclinical or clinical scores as defined in the manual are the same for maternal and paternal ratings, children rated by their mother will more often pass the threshold than children rated by their father due to this difference between raters.…”
Section: Discussionsupporting
confidence: 91%
“…The outcome of these assessments can depend on the rater. Earlier studies in 7‐year‐old children have found maternal ratings to be higher than paternal ratings [Duhig et al, ; van der Valk et al, ; Luoma et al, ; Boomsma et al, ; Abdellaoui et al, ; Langberg et al, ; Mascendaro et al, ; Sollie et al, ]. The ranking of the children's problems has also been found to vary between fathers and mothers resulting in correlations of 0.60 between maternal and paternal ratings [Achenbach et al, ; Duhig et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dominant (non-additive) genetic influences have not been reported for this age group (Edelbrock et al 1995; Schmitz et al 1995; Polderman et al 2006; Abdellaoui et al 2008; Lin et al 2006; Kuo et al 2004). These estimates were based on parental or teacher ratings of children’s behavior.…”
Section: Introductionmentioning
confidence: 94%
“…These estimates were based on parental or teacher ratings of children’s behavior. The study with the largest sample size (~9,000 7-year old twin pairs) estimated the heritability at 61% and 65% for ratings from the twins’ mothers and fathers, respectively (Abdellaoui et al 2008). This study also concluded that the rater agreement on TP between the parents was 67%, while the remaining 33% consisted of a unique view on the phenotype and/or measurement error.…”
Section: Introductionmentioning
confidence: 99%